2019
DOI: 10.1111/jcpe.13201
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of minimally invasive periodontal surgery in the treatment of infrabony defects: Systematic review and meta‐analysis

Abstract: Aim To assess the effectiveness, in terms of clinical performance and patient perception, of minimally invasive periodontal surgeries (MIPSs), and to compare MIPSs to traditional surgery in the treatment of periodontal infrabony defects. Materials and Methods An electronic search and a manual search were carried out to identify studies investigating clinical (CAL, PPD, REC), radiographic (bone fill) and patient's centred (VAS) outcomes at least 6 months after MIPSs. A linear mixed‐effect model was used for met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 51 publications
6
28
0
2
Order By: Relevance
“…Slightly more dated systematic reviews on this topic have also shown us that: i) minimally invasive flaps lead to improved clinical and radiographic outcomes compared with larger flaps (‘traditional’ approaches) (Clementini et al, 2019); ii) when minimally invasive flaps are employed, the addition of biomaterials does not seem to improve clinical outcomes (Liu et al, 2016).…”
Section: Paper Focus Comparison Main Inclusions Methods Main Results Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slightly more dated systematic reviews on this topic have also shown us that: i) minimally invasive flaps lead to improved clinical and radiographic outcomes compared with larger flaps (‘traditional’ approaches) (Clementini et al, 2019); ii) when minimally invasive flaps are employed, the addition of biomaterials does not seem to improve clinical outcomes (Liu et al, 2016).…”
Section: Paper Focus Comparison Main Inclusions Methods Main Results Conclusionmentioning
confidence: 99%
“…These are important outcomes trying to answer the question about predictability: 'In how many cases will using a regenerative approach with biomaterials lead to the desired clinical outcome (translating into tooth retention long-term)?' Slightly more dated systematic reviews on this topic have also shown us that: i) minimally invasive flaps lead to improved clinical and radiographic outcomes compared with larger flaps ('traditional' approaches) (Clementini et al, 2019); ii) when minimally invasive flaps are employed, the addition of biomaterials does not seem to improve clinical outcomes (Liu et al, 2016).…”
mentioning
confidence: 99%
“…e microsurgical approach facilitated gentle handling of tissues and precise wound closure, resulting in a > 90% rate of primary closure reported by some studies [120][121][122]. Other advantages include improved visual acuity, enhanced revascularization, and maximum preservation of the tissue [123,124]. Various double-layer suturing approaches have been suggested when a microsurgical approach is used [120,125,126].…”
Section: Minimally Invasive Surgical Therapymentioning
confidence: 99%
“…Subsequent systematic reviews and meta-analyses have established that regenerative outcomes with a minimally International Journal of Dentistry invasive surgery are superior to access flaps [28,124]. Furthermore, the additional use of biomaterials or membranes has been used in combination with a minimally invasive surgery with successful outcomes of up to six years and low postsurgical morbidity [31,[132][133][134][135][136][137] but does not appear to enhance regenerative outcomes, indicating enhanced healing potential with a minimally invasive surgical approach [138][139][140][141].…”
Section: Minimally Invasive Surgical Therapymentioning
confidence: 99%
“…It has been reported that with M‐MIST, in particular, significant tissue regeneration even without the use of adjunctive biomaterials was achieved, suggesting that it is an excellent modality that promotes periodontal tissue regeneration 24 . The enhanced tissue regenerative effect of minimally invasive approaches is statistically demonstrated in systematic reviews and meta‐analyses 25,26 …”
Section: Introductionmentioning
confidence: 99%